Implementation of Outdoor Learning Activity (OLA) to Develop Motor Ability of Early Childhood - Khusnul Laely; Lilis Madyawati; Hermahayu Hermahayu; Syakila Fatkhia Rizki; Chomisah Nugraheni (Universitas Negeri Semarang, 2023)
This study aims to describe the implementation of outdoor learning activity (OLA) to develop motor skills in early childhood. The research approach uses a qualitative descriptive method in the form of a survey. The subjects in this study were educators of Early Childhood Education (PAUD) institutions under the auspices of the Bustanul Athfal Teachers Association (IGABA), Raudhatul Athfal Teachers Association (IGRA) and Himpaudi Magelang Regency, totaling 40 educators both teaching kindergarten, RA/ BA, Playgroup and Child Care Center (TPA). The data collection tool used is a questionnaire by respondents in the FGD event to identify the implementation of OLA in developing motor skills of early childhood. In this survey research, researchers used quantitative data analysis techniques with a descriptive approach. The results of the study indicate that activities that develop motor skills have been implemented in Outdoor Learning Activity (OLA) by implementing demonstration methods, hands-on practice, field trips, playing methods, project methods, and assignments. A complete understanding of the understanding of OLA is playing outdoors by designing fun activities with the aim of getting sunlight, only reaching 6% as evidenced by 27.03% of educators who just implement OLA every day to get sunlight.